Augmented Reality in Educational Environments: A Systematic Review - Sharma, Shivam; Tuli, Neha; Mantri, Archana (Journal of Engineering Education Transformations, 2022)
This study focuses on the emerging technologies used in Augmented Reality (AR) and their role in the field of education. With this aim, 70 articles gathered from Scopus, Science Direct, Springer, Taylor Francis, and Web of science databases were examined. Analysis showed that the number of AR articles in educational environments have gradually increased over the years. AR is being most commonly used in science education (biology, physics and chemistry). The literature also highlights various advantages of AR when used in learning environments. It has been understood that the AR is an imminent learning tool and is lately gaining recognition and acceptance in the educational field. While marker-based AR was the key in most of the articles, it was implemented using mobile devices. The literature revealed that most articles examined their results using Quantitative methods. Our article emphasizes on the impact of AR in education, current technologies and its future scope. This paper also provides detailed analysis of the use of AR in engineering education highlighting that the most of the articles highlighted the use of marker-based AR, used non-probability sampling strategy and applied mixed method for analysis. The findings of this study would help other researchers to identify potential direction for future research.